2020
DOI: 10.1186/s40168-020-00799-9
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere protists are key determinants of plant health

Abstract: Background: Plant health is intimately influenced by the rhizosphere microbiome, a complex assembly of organisms that changes markedly across plant growth. However, most rhizosphere microbiome research has focused on fractions of this microbiome, particularly bacteria and fungi. It remains unknown how other microbial components, especially key microbiome predators-protists-are linked to plant health. Here, we investigated the holistic rhizosphere microbiome including bacteria, microbial eukaryotes (fungi and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 198 publications
(131 citation statements)
references
References 61 publications
2
110
0
3
Order By: Relevance
“…Plant tissues were fully ground into powder in a mortar with liquid nitrogen. Then DNA was extracted from rice samples and bulk soil using the PowerSoil DNA isolation kit (Mo Bio Laboratories) as per the manufacturer’s instructions [ 31 , 32 ]. DNA was quantified with a Qubit Fluorometer by using the Qubit dsDNA BR Assay kit (Life technologies, USA) and the quality was assessed by running an aliquot on a 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…Plant tissues were fully ground into powder in a mortar with liquid nitrogen. Then DNA was extracted from rice samples and bulk soil using the PowerSoil DNA isolation kit (Mo Bio Laboratories) as per the manufacturer’s instructions [ 31 , 32 ]. DNA was quantified with a Qubit Fluorometer by using the Qubit dsDNA BR Assay kit (Life technologies, USA) and the quality was assessed by running an aliquot on a 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that protists play important roles in the soil microbiome and in plant health (Thakur and Geisen, 2019). For example, Xiong et al (2020) found that the pathogen dynamics is best predicted by protists, which were found to be negatively correlated with pathogen abundance during the growth of tomato plants. By directly feeding on the pathogen or indirectly by inducing shifts in the taxonomic and functional composition of bacteria via predation, protists might provide plant protection.…”
Section: Current Challenges and Future Perspectives For Exploiting Thmentioning
confidence: 99%
“…This is, for example, the case of Sphagnum and peatland-mosses-associated protists for which both V4 (TAReuk) and V9 (1380F/1510R) primers have been used [ 137 , 138 ]. Both V4 (V4_1f/TAReukREV3) and V9 (1380F/1510R) primers have also been employed to study rhizospheric protists [ 139 , 140 ]. Although plant sequences could represent the majority of reads in such plant-associated protist metabarcoding datasets, strategies to reduce the co-amplification of the associated plant(s), for example, the utilization of blocking oligos, have not yet been implemented.…”
Section: Amplicon Library Preparationmentioning
confidence: 99%